Influence of Social Networks Sites on Latin American Democracy - León Ganatios, Luis Eduardo (2024)
Social networking sites have had a significant impact on politics and democracy. They can bring about positive changes that contribute to establishing a more effective and complete democracy. In this study, we investigate the relationship between social networks and democratic effectiveness in Latin American countries. We conducted a quantitative and inferential statistical analysis using representative surveys from2023 to demonstrate that the internet and social networks have a notable impact on the democratization process of these countries. Our study challenges the hypothesis proposed by Lipset that a nation’s economic prosperity contributes to strengthening democracy.